DOI: 10.29007/rl4h
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression networks uncover regulation of splicing and transcription markers of disease

Abstract: Gene co-expression networks based on gene expression data are usually used to capture biologically significant patterns, enabling the discovery of biomarkers and interpretation of regulatory relationships. However, the coordination of numerous splicing changes within and across genes can exert a substantial impact on the function of these genes. This is particularly impactful in studies of the properties of the nervous system, which can be masked in the networks that only assess the correlation between gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Differential abundance of splice variants annotated to receptors, ion channels and growth factors associated with nociception and pain have been reported [17][18][19]. Our targeted study of circadian rhythm and toll-like receptor networks demonstrated the transcript isoform profiling can offer additional insights on OIH [12]. Moreover, alternative splicing impacts the function of genes in many pathways involved in OIH such as glutamatergic and myelination processes.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…Differential abundance of splice variants annotated to receptors, ion channels and growth factors associated with nociception and pain have been reported [17][18][19]. Our targeted study of circadian rhythm and toll-like receptor networks demonstrated the transcript isoform profiling can offer additional insights on OIH [12]. Moreover, alternative splicing impacts the function of genes in many pathways involved in OIH such as glutamatergic and myelination processes.…”
Section: Introductionmentioning
confidence: 81%
“…The isoform-level output from STAR was subsequently processed in RSEM (v. 1.3.1) to quantify the transcript isoform expression in raw reads counts [26]. This pipeline differed from our previous analysis [10,12,23] and optimized the quantification of expression at the transcript isoform level.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternative Splicing (AS) is known to be a tightly-regulated process in which splicing factors interact to create cell type-specific isoform expression patterns 78 . The transcriptome-level consequences of AS regulation have been studied in different ways, including, but not limited to, the detection of within-isoform coordination of alternative sites 40,41 , the generation of gene-isoform networks to uncover novel regulatory relationships [79][80][81][82] and the application of single-cell data to unravel cell type-specific expression patterns for same-gene isoforms 27,83 . However, the extent to which AS regulation creates co-expression patterns among alternative isoforms from different genes has not yet been fully addressed.…”
Section: Discussionmentioning
confidence: 99%